Modulation of leukotriene signaling inhibiting cell growth in chronic myeloid leukemia. Issue 8 (3rd August 2017) - Yektaei-Karin, Elham; Zovko, Ana; Nilsson, Anders; Näsman-Glaser, Barbro; Kanter, Lena; Rådmark, Olof; Wallvik, Jonas; Ekblom, Marja; Dolinska, Monika; Qian, Hong; Stenke, Leif
Abstract: Although tyrosine kinase inhibitors (TKIs) have dramatically improved clinical outcome in chronic myeloid leukemia (CML), cure rarely occurs. This may be due to BCR-ABL -independent, aberrant signaling pathways, one of which leads to leukotriene (LT) formation. Well-recognized as inflammatory mediators, LT can also affect oncogenic mechanisms of several tumors. We have previously discovered elevated LT-synthesis and up-regulated cysteinyl-LT-inducing enzyme in CML. Here we report on dose-dependent inhibition of CML cell growth exerted by specific blockers of LT-signaling. Thus, the cysteinyl-LT1-receptor-antagonist montelukast significantly reduced the growth of K562, KCL22, and KU812 cells, as well as primary CD34 + blood cells from two CML patients. Adding montelukast to the TKI imatinib caused combined inhibition. No effect was seen on normal bone marrow cells. Similarly, growth inhibition was also observed with the 5-lipoxygenase (LO)-inhibitor BWA4C, the 5-LO-activating-protein-(FLAP)-inhibitor licofelone and the LTB4 (BLT1)-receptor-antagonist LY293111. Thus, blocking of aberrant LT-signaling may provide an additional, novel therapeutic possibility in CML.